การพัฒนาบทเรียนอีเลิร์นนิงวิชาภาษาอังกฤษเพื่อการสื่อสาร ตามสภาพแวดล้อม การเรียนส่วนบุคคลบนอินเทอร์เน็ตผ่านทางเครือข่ายสังคม สำหรับนักศึกษาปริญญาตรี - แสงหล่อ แกมกาญจน์ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อ (1) พัฒนาบทเรียนอีเลิร์นนิงวิชาภาษาอังกฤษเพื่อการสื่อสาร ให้มีประสิทธิภาพไม่ต่ำกว่า 80/80 (2) เพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนก่อนและหลังเรียนจากบทเรียนที่พัฒนาขึ้น (3) เพื่อหาค่าดัชนีประสิทธิผลจากการเรียนด้วยบทเรียนที่พัฒนาขึ้น (4) เพื่อเปรียบเทียบความคงทนในการเรียนรู้ เมื่อเรียนผ่านไป 2 และ 4 สัปดาห์ และ (5) เพื่อศึกษาความพึงพอใจต่อการเรียนจากบทเรียนอีเลิร์นนิงที่พัฒนาขึ้น ประชากรเป็นนักศึกษาคณะครุศาสตร์ มหาวิทยาลัยสวนดุสิต วิทยาเขตสุพรรณบุรี ชั้นปีที่ 1 ปีการศึกษา 2558 จำนวน 80 คน และใช้การสุ่มอย่างง่ายด้วยการจับฉลาก จำนวน 72 คน เป็นกลุ่มพัฒนาบทเรียนอีเลิร์นนิง จำนวน 42 คน และกลุ่มทดลองในการวิจัย จำนวน 30 คน ผลการวิจัยพบว่า (1) บทเรียนที่พัฒนาขึ้นมีประสิทธิภาพเท่ากับ 80.33/81.89 ซึ่งเป็นไปตามเกณฑ์ (2) ผลสัมฤทธิ์ทางการเรียนหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 (3) ค่าดัชนีประสิทธิผลเท่ากับ 0.701(4) ความคงทนในการเรียนรู้ เมื่อเรียนผ่านไป 2 และ 4 สัปดาห์ แตกต่างกันอย่างไม่มีนัยสำคัญทางสถิติ และ (5) ความพึงพอใจของนักศึกษาต่อการเรียนจากบทเรียนอีเลิร์นนิงที่พัฒนาขึ้น อยู่ในระดับความพึงพอใจมาก สรุปได้ว่า สรุปได้ว่าบทเรียนอีเลิร์นนิงที่พัฒนาขึ้น มีประสิทธิภาพสูง มีประสิทธิผลดี และมีความพึงพอใจอยู่ในระดับมาก และสามารถนำไปใช้ในการเรียนการสอนได้ คำสำคัญ: บทเรียนอีเลิร์นนิง สภาพแวดล้อมการเรียนส่วนบุคคล การวิจัยและพัฒนา เครือข่ายสังคม ภาษาอังกฤษเพื่อการสื่อสาร ABSTRACT The purposes of this research were: (1) to develop e-Learning in English for communication lesson to meet the 80/80 efficiency criterion, (2) to compare learning achievement scores before and after studying from developed e-Learning, (3) to verify an effectiveness index of the developed e-Learning to not less than 0.70 criteria, (4) to examine students’ retention after completing the course for 2 and 4 weeks, and (5) to study the students’ satisfaction towards the developed e-Learning. The population was 80 first year undergraduates, who were studying in the semester of 2015 at Faculty of Education, SuanDusit University, SuphanBuri Campus, Thailand. The samples used in this research consisted of 72 students derived from simple random sampling, divided into the group of 42 students developing the e-Learning Lessons, and 30 students for conducting the experiment. The research results were as follows: (1) the developed e-Learning achieved the efficiency at 80.33/81, as the purposive criterion, (2) an effectiveness index was 0.701, (3) a comparison of students’ achievement found that the post test learning achievements were higher than the pre-test, statistically significant at the 0.05 level, (4) the learning retention gained after completing the course for 2 weeks and 4 weeks later were not statistically significant difference and (5) the average students’ satisfaction was at a high level(=3.57, S.D.=0.75). As a result, it could be concluded that the developed e-Learning lessonswere highly efficient, well effective, and high satisfactory, and it should be used as a part of the undergraduate curriculum. Keywords: E-Learning, Personal Learning Environment, Research and Development, Social Network, English for Communication